Osteohistological characterization of notosuchian osteoderms: Evidence for an overlying thick leathery layer of skin - Sena, Mariana Valéria de Araújo (2023)
Osteoderms are mineralized structures embedded in the dermis, known for nonavian archosaurs, squamates, xenarthrans, and amphibians. Herein, we compared the osteoderm histology of Brazilian Notosuchia of Cretaceous age using three neosuchians for comparative purposes. Microanatomical analyses showed that most of them present a diploe structure similar to those of other pseudosuchians, lizards, and turtles. This structure contains two cortices (the external cortex composed of an outer and an inner layers, and the basal cortex) and a core in-between them. Notosuchian osteoderms show high bone compactness (>0.85) with varying degrees of cancellous bone in the core. The neosuchian Guarinisuchus shows the lowest bone compactness with a well-developed cancellous layer. From an ontogenetic perspective, most tissues are formed through periosteal ossification, although the mineralized tissues observed in baurusuchid LPRP/USP 0634 suggest a late metaplastic development. Histology suggests that the ossification center of notosuchian osteoderm is located at the keel. Interestingly, we identified Sharpey's fibers running perpendicularly to the outer layer of the external cortex in Armadillosuchus arrudai, Itasuchus jesuinoi, and Baurusuchidae (LPRP/USP 0642). This feature indicates a tight attachment within the dermis, and it is evidence for the presence of an overlying thick leathery layer of skin over these osteoderms. These data allow a better understanding of the osteohistological structure of crocodylomorph dermal bones, and highlight their structural diversity. We suggest that the vascular canals present in some sampled osteoderms connecting the inner layer of the external cortex and the core with the external surface may increase osteoderm surface and the capacity of heat transfer in terrestrial notosuchians.